Comunicação E Esfera Pública: Análise Da Cobertura Do Jornal Folha De S.Paulo (Versão Online) Sobre A Reorganização Escolar (2015) E As Ocupações Secundaristas - Canesin, Eduardo Marangoni [UNIFESP] (2018)
The Master"S Thesis Identifies And Characterizes The Speeches Published In Folha De S.Paulo Newspaper (Online Version) About The School Reorganization Proposition (2015) And The High School Students Occupations, Undertaken By Consequence. Qualitatively Analyzes The Articles Published About The Subject And Reflects About The Changes In The Coverage, Searching Explanation For This: At The Beginning It Was Against To The Protests, Passing, After That, To Support Them (Even If Does Not Change It"S Position About Public Policy Itself). Intend, That Way, Make A Deeper Analysis About Sociology Of Communication, Analysing The Press Role, Nowadays, In The Construction Of A Rational-Critical Debate And Strengthening Of The Public Sphere, At The Same Time That Is Stage For Symbolic Disputes. Discusses That There Are No Vector Imposition Of World Visions (Leastwise There Is Not Only This), That Will Be Passively Accepted By The Public (Although There Are Bias And Asymmetry Of Forces). There Is A More Complex Relation In